2019
DOI: 10.1590/1678-992x-2017-0334
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient digestibility and changes in feeding behavior of cattle fed cottonseed and vitamin E

Abstract: High lipid concentration in ruminant diets often harms nutrient digestibility and feed intake; thus, a protected lipid and antioxidant source can be considered as an alternative for improving diet energy without putting animal production at a disadvantage. The aim of this study was to evaluate the dry matter intake (DMI), nutrient digestibility and feeding behavior of cattle fed cottonseed and vitamin E. Six cannulated cows, non-pregnant, non-lactating were distributed in a replicated 3 × 3 Latin Square design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…An increased tendency of rumen pH is recorded (p=0.05) with LO addition compared to CON values whereas VE inclusion did not change pH values compared to those fed on LO. Numerically higher ruminal pH on feeding LO was in agreement with previous studies using different lipid sources including fish oil in diets of sheep (Wachira et al, 2000), in diet of cows (Shingfield et al, 2003) and both of these studies attributed this increase to associated decreases in DMI and also in diets of cattle fed cottonseed alone or combined with vitamin E (Nogueira et al, 2019) and they explained higher pH to higher NDF content of cottonseed. On the other hand, Gawad et al (2015) recorded lower ruminal pH values in vitro with different levels of linseed oil beads but they suggested that the mean of pH values remained within normal range of pH which is between (6 and 6.7).…”
Section: Ruminal Parameterssupporting
confidence: 91%
“…An increased tendency of rumen pH is recorded (p=0.05) with LO addition compared to CON values whereas VE inclusion did not change pH values compared to those fed on LO. Numerically higher ruminal pH on feeding LO was in agreement with previous studies using different lipid sources including fish oil in diets of sheep (Wachira et al, 2000), in diet of cows (Shingfield et al, 2003) and both of these studies attributed this increase to associated decreases in DMI and also in diets of cattle fed cottonseed alone or combined with vitamin E (Nogueira et al, 2019) and they explained higher pH to higher NDF content of cottonseed. On the other hand, Gawad et al (2015) recorded lower ruminal pH values in vitro with different levels of linseed oil beads but they suggested that the mean of pH values remained within normal range of pH which is between (6 and 6.7).…”
Section: Ruminal Parameterssupporting
confidence: 91%
“…Decreased DM intake can be expected when dietary fat concentration exceeds 6% (Martin et al, 2010). However, Nogueira et al (2019) added 8% fat concentration to cow feed and did not observe any difference in DMI between treatments. According to Joy et al (2021), increasing the lipid content of the diet of beef heifers improves palatability and feed efficiency and increases the energy density of the diet.…”
Section: Discussionmentioning
confidence: 83%
“…According to NRC ( 2001), feeding polyunsaturated oils as part of a whole-oilseed diet has minimal effects on fermentation, probably because the oil is released slowly from the seed to ruminal fluid. This phenomenon occurs with the WCS, where the polyunsaturated FAs are protected inside the seed, requiring greater effort of rumination and mastication for its release (Nogueira, Perna, Pereira, & Rodrigues, 2019), providing small amounts of lipids in the ruminal environment, which may result in rapid BH, avoiding unsaturated FA accumulation and impairment of the ruminal degradation of the fiber. Moreover, the amount will not be enough to adhere to feed particles, causing physical impediment to microorganisms and microbial enzymes (Bettero et al, 2013).…”
Section: Discussionmentioning
confidence: 99%